Single Branding as a Digital Marketing Communication Strategy for Tempo Media Group - Sumardi, Eko (Communication, 2026)
In the digital era, mass media in Indonesia face declining advertising revenue. The majority of digital advertising expenditure flows to Google (YouTube) and Meta (Facebook and Instagram), rather than to local media. Under these challenging conditions, single branding has become one of the digital marketing communication strategies for media sustainability. This study examines how the implementation of a single brand serves as a digital marketing communication strategy for Tempo Media Group by unifying its three digital journalistic products, namely tempo.co, koran.tempo.co, and majalah.tempo.co. The study employs a qualitative descriptive approach based on qualitative data. The data were collected through interviews, document tracking, and digital observations from official sources and related official websites. The researcher applies Sicco van Gelder’s Brand Expression Theory, emphasizing the importance of positioning, identity, and brand personality to strengthen market position. The findings indicate that Tempo implements its single brand by applying the digital-first principle, whereby digital subscribers receive articles prior to the print version, which is published weekly on Mondays. Tempo subscribers also receive the Tempo Plus product, which provides access to Teras Plus and The New York Times. The study concludes that the implementation of Tempo’s single brand through the integration of tempo.co, koran.tempo.co and majalah.tempo.co enables Tempo to be more responsive in addressing readers’ needs and preferences regarding news consumption.